Delusional misidentification in Parkinson's disease: report of two cases and a review. Issue 2 (17th February 2018) - Hermanowicz, Neal
ABSTRACT: Syndromes of delusional misidentification consist of disordered familiarity and have been reported in diverse diagnoses, including Parkinson's disease. Although the most common delusional misidentification is Capgras syndrome, in which the sufferer believes a familiar person has been replaced by an identical imposter, other forms have been also described. The pathogenesis of delusions of misidentification appears to require dysfunction of or connection to a left cerebral cortical area involved in recognition of familiarity, and also right frontal cortex serving belief evaluation. Two cases of Parkinson's disease with an unusual delusional misidentification, intermetamorphosis, are presented, along with their improvement with pimavanserin, a novel atypical antipsychotic medication.